Strategi Pembelajaran Kreatif dalam Meningkatkan Minat Baca Siswa Sekolah Dasar - Kris Jernih Puspita Ziliwu; Sapnia Wahyu Ramadani Damanik; Novi Wulandari; Lerin Doloksaribu (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Elementary school students' interest in reading is an important aspect in the ongoing learning process. However, students' low interest in reading is a challenge for educators. This article aims to examine various creative learning strategies that can be applied to increase elementary school students' interest in reading. Using the literature review method, this article identifies and analyzes effective learning strategies in the context of basic education.